دور القاضي الإداري فى رقابة مبدأ تناسب الجزاء التأديبى - لعلام، محمد مهدي Lallam, Mohammed Mahdi (احمد عبد الصبور الدلجاوي, 2015)
تمثل العقوبة التأديبية في مجال الوظيفة العامة القرار التأديبي الذي يخضع لنفس القواعد التي تخضع لها سائر القرارات الإدارية المعروفة في مجال المنازعات الإدارية، وبذلك تعد المنازعات الوظيفية من أكثر المنازعات الإدارية شيوعا وأهمية. ولهذا كان موضوع مبدأ التناسب في الجزاءات التأديبية أحد جزئيات المنازعات الوظيفية التي أثارت اختلافا كبيرا بين الفقه والقضاء الإداريين بين مؤيد ورافض. وفي سبيل الحصول على عقوبة عادلة ومنصفة، لابد من مراعاة واحترام السلطة التأديبية لهذا المبدأ، خاصة وأنه يساعد في التوازن بين مبدأ فاعلية الإدارة في أداء واجباتها وانضباط في العمل، ومبدأ ضمان حق الموظف العام في حصوله علة عقوبة عادلة.
The disciplinary sanction in the public function is a disciplinary decision submitted to the same rules of the other administrative decisions in the administrative litigation. Therefore, litigation of the public service is considered among the most frequently matter. For this, the problem of the principle of proportionality in action discipline is one of the litigation that makes a big difference between the case law and judicial decisions. The proportionality principle how best to ensure a fair punishment and equitable vis-à-vis the mistakes committed by the official. and upshot administrative efficiency in the performance of these functions and discipline in working to ensure the rights of the employee.
Keywords: القوانين والتشريعات -- الرقابة القضائية -- القضاء الإدارى -- الجزاءات التأديبية -- المغرب